Hematological status and endurance performance predictors after low altitude training supported by normobaric hypoxia: a double-blind, placebo-controlled study - Sitkowski, D.; Szygula, Z.; Surala, O.; Orysiak, J.; Zdanowicz, R.; Pokrywka, A.; Starczewski, M.; Malczewska-Lenczowska, J. (Biology of Sport, 2019)
The benefits of altitude/hypoxic training for sea level performance are still under debate. This study examined the effects of low altitude training supported by normobaric hypoxia on hematological status and endurance performance predictors in elite female cyclists. Twenty-two female cyclists trained for 3 weeks at low altitude (<1100 m) and 2 weeks near sea level. During the first 3 weeks, 15 subjects stayed in hypoxic rooms simulating an altitude of 2200 m (+NH group, n = 8) or 1000 m (placebo group, n = 7), and 7 (control group) stayed in regular rooms. Significant increases in total hemoglobin mass (tHb-mass: p = 0.008, p = 0.025), power at 4 mmol·l-1 lactate (PAT4: p = 0.004, p = 0.005) (in absolute and relative values, respectively) and maximal power (PF: p = 0.034) (in absolute values) were observed. However, these effects were not associated with normobaric hypoxia. Changes in tHb-mass were not associated with initial concentrations of ferritin or transferrin receptor, whereas changes in relative tHb-mass (r = -0.53, p = 0.012), PF (r = -0.53, p = 0.01) and PAT4 (r = -0.65, p = 0.001) were inversely correlated with initial values. Changes in tHb-mass and PAT4 were positively correlated (r = 0.50, p = 0.017; r = 0.47, p = 0.028). Regardless of normobaric hypoxia application, low altitude training followed by sea-level training might improve hematological status in elite female cyclists, especially with relatively low initial values of tHb-mass, which could translate into enhanced endurance performance.